Role of IMF By in the prompt electric field disturbances over equatorial ionosphere during a space weather event. Issue 2 (23rd February 2017) - Chakrabarty, D.; Hui, Debrup; Rout, Diptiranjan; Sekar, R.; Bhattacharyya, Archana; Reeves, G. D.; Ruohoniemi, J. M.
Abstract: On 7 January 2005 ( A p =40) prompt penetration electric field perturbations of opposite polarities were observed over Thumba and Jicamarca on a few occasions during 13:45–16:30 UT. However, the electric field was found to be eastward during 14:45–15:30 UT over both Thumba and Jicamarca contrary to the general expectation wherein opposite polarities are expected at nearly antipodal points. On closer scrutiny, three important observational features are noticed during 14:10–15:15 UT. First, during 14:10–14:45 UT, despite increasing southward interplanetary magnetic field (IMF) B z condition, the already westward electric field over Thumba weakened (less westward) while the eastward electric field over Jicamarca intensified (more eastward). Second, the electric field not only became anomalously eastward over Thumba but also got intensified further during 14:45–15:00 UT similar to Jicamarca. Third, during 15:00–15:15 UT, despite IMF B z remaining steadily southward, the eastward electric field continued to intensify over Thumba but weakened over Jicamarca. It is suggested that the changes in IMF B y component under southward IMF B z condition are responsible for skewing the ionospheric equipotential patterns over the dip equator in such a way that Thumba came into the same DP2 cell as that of Jicamarca leading to anomalous electric field variations. Magnetic field measurements along the Indian and Jicamarca longitude sectors and changes in high‐latitude ionospheric convection patterns provide credence to this proposition. Thus, the present investigation shows that the variations in IMF B y are fundamentally important to understand the prompt penetration effects over low latitudes. Key Points: Identical polarity of penetration electric field over Thumba and Jicamarca Role of IMF B y in determining polarity of prompt penetration electric field Changes in IMF B y distort DP2 cells to bring antipodal stations (Thumba and Jicamarca) in the same cell